Computing and classifying reduplication with 2-way finite-state transducers - Dolatian, Hossep; Heinz, Jeffrey (Journal of Language Modelling, 2020)
This article describes a novel approach to the computational modeling of reduplication. Reduplication is often treated as a stumbling block within finite-state treatments of morphology because they cannot adequately capture the productivity of unbounded copying (total reduplication) and because they cannot describe bounded copying (partial reduplication) without a large increase in the number of states. We provide a comprehensive typology of reduplicative processes and show that an understudied type of finite-state machine, 2-way deterministic finite-state transducers (2-way D-FSTs), captures virtually all of them. Furthermore, the 2-way D-FSTs have few states, are in practice easy to design and debug, and are linguistically motivated in terms of the transducer’s origin semantics or segment alignment. Most of these processes, and their corresponding 2-way D-FSTs, are available in an online database of reduplication (RedTyp). We classify these 2- way D-FSTs according to the concatenation of known subclasses of regular relations and show that the majority fall into the Concatenated Output Strictly Local (C-OSL) class. Other cases require higher subclasses but are still definable by 2-way D-FSTs.